PENGARUH PERCEIVED VALUE, RELATIONSHIP MARKETING, DAN BRAND IMAGE TERHADAP LOYALITAS PELANGGAN PADA LINKS CAFE MEDAN - Clara Nadia Yunan; Arifin (MTU PRESS, 2023)
The food and beverage industry business in Indonesia has increased rapidly over the last few years. Links Café, a simple and comfortable cafe that opened in the middle of the city of Medan, pays attention to factors that can maintain and increase the number of customers who continue to visit Links Café. The purpose of this research is to find out whether Perceived Value (X1), Relational Marketing (X2), and Brand Image (X3) have an effect on customer loyalty (Y) at Links Café, Medan. The population selected in this research were customers who had visited or purchased at Links Café, with a total sample of 97 respondents using a non-probability sampling method. The approach used in this research is quantitative, causal and descriptive. Several test instruments, descriptive analysis, classical assumption tests, multiple linear regression, coefficient of determination tests, and hypothesis tests are used in the research process. The data from the analysis produces a multiple linear regression equation Y=5.528 + 0.275X1 + 0.132X2 + 0.447X3 + 2.375. This shows that Brand Image (X3) has a greater influence on the attachment variable than X1 and X2. The T test and F test produce Perceived Value (X1), Relational Marketing (X2), and Brand Image have a significant and positive effect on Customer Loyalty (Y), resulting in the hypotheses H1, H2, H3, and H4 being accepted. The coefficient of determination shows that the three independent variables have an influence of 69.4%, while the other 30.6% is influenced by other factors not examined in the research. Therefore, to increase customer loyalty, Links Café can improve its services to pay more attention to customers and give customers a stronger impression.